Effect of Azadirachta excelsa and Melia azedarach extracts on soybean germination - RUMMI AZAHRA GUMILAR; NURHENI WIJAYANTO; ARUM SEKAR WULANDARI (Nusantara Bioscience, 2017)
Gumilar RA, Wijayanto N, Wulandari AS. 2017. Effect of Azadirachta excelsa and Melia azedarach extracts on soybean germination. Nusantara Bioscience 9: 346-351. Azadirachta excelsa and Melia azedarach are potential tree species developed in agroforestry system. Both plants are fast growing species and good for timber use. However, there is an inadequacy on both species due to their allelopathic compound contents. Allelopathic compounds in the plants are distributed from root, stem, leaf, and fruit; which at certain concentrations could inhibit germination, growth, and development of other plants. The objective of this study was to analyze the effects of root, leaf, and twig extracts of M. azedarach and A. excelsa on the germination of soybean. Result of this study showed that the root, leaf, and twig extracts of M. azedarach and A. excelsa were able to inhibit the development of soybean. 5 % twig extract of M. azedarach significantly inhibited the germination by 77.75%. Leaf and twig extracts of A. excelsa at 1.25% concentration has shown to provide stimulant effect on the germination of soybean.